MENGUNYAH PERMEN KARET SEBAGAI TERAPI MODALITAS UNTUK PERCEPATAN PEMULIHAN PASCA OPERASI SESAR - Putra, Andi Budiyanto Adi; Arifuddin, Fitrawati (Universitas Islam Negeri Alauddin Makassar, 2017)
Caesarean Section is the most common surgery leading to decrease bowel movement and brings gastrointestinal problems. Some studies explore the use of gum chewing in the hasten of gastrointestinal motility after cesarean section. This modality continues to be known as one of modality in solving gastrointestinal problem after abdominal surgery. This simple and easy intervention has shown big influence and benefit. However, in Indonesia remain unknown. The purpose of this reviews is to describe chewing gum and its mechanism in reducing gastrointestinal problems following caesarean section. This paper reviews articles cited from literature searching include ProQuest, EBSCO HOST, Science Direct, dan other searching engine Google. We identified 34 abstracts, after screening a total of 8 studies met the inclusion criteria with 5 RCTs and 3 systematic reviews. The result shows that this modality can fasten the recovery time and supports faster oral intake, it also can give effect on decreasing length of hospital stay and cost for its harmless, easy, benefit and inexpensive. In conclusion, the use of gum chewing after caesarean section has been demonstrated as modality to support the hasten of gastrointestinal motility after caesarean surgery.